Book review: Clammer, John. 2015: Art, Culture and International Development: Humanizing Social Transformation. (July 2016) - Walker, Margath A.
Clammer, John. 2015: Art, Culture and International Development: Humanizing Social Transformation. London and New York: Routledge. 168 pp. £90.00 (hardback), £48.93 (paperback), £25.64 (ebook). ISBN: 978 1 138 02471 7 (hardback), 978 1 138 02472 4 (paperback), 978 315 77555 5 (ebook).